Acute desensitization of GIRK current in rat atrial myocytes is related to K(+) current flow - Bender, Kirsten (Blackwell Science Inc, 2004)
We have investigated the acute desensitization of acetylcholine-activated GIRK current (I(K(ACh))) in cultured adult rat atrial myocytes. Acute desensitization of I(K(ACh)) is observed as a partial relaxation of current with a half-time of < 5 s when muscarinic M(2) receptors are stimulated by a high concentration (> 2 μmol l(−1)) of ACh. Under this condition experimental manoeuvres that cause a decrease in the amplitude of I(K(ACh)), such as partial block of M(2) receptors by atropine, intracellular loading with GDP-β-S, or exposure to Ba(2)(+), caused a reduction in desensitization. Acute desensitization was also identified as a decrease in current amplitude and a blunting of the response to saturating [ACh] (20 μmol l(−1)) when the current had been partially activated by a low concentration of ACh or by stimulation of adenosine A1 receptors. A reduction in current analogous to acute desensitization was observed when ATP-dependent K(+) current (I(K(ATP))) was activated either by mitochondrial uncoupling using 2,4-dinitrophenole (DNP) or by the channel opener rilmakalim. Adenovirus-driven overexpression of Kir2.1, a subunit of constitutively active inwardly rectifying K(+) channels, resulted in a large Ba(2)(+)-sensitive background K(+) current and a dramatic reduction of ACh-activated current. Adenovirus-driven overexpression of GIRK4 (Kir3.4) subunits resulted in an increased agonist-independent GIRK current paralleled by a reduction in I(K(ACh)) and removal of the desensitizing component. These data indicate that acute desensitization depends on K(+) current flow, independent of the K(+) channel species, suggesting that it reflects a reduction in electrochemical driving force rather than a bona fide signalling mechanism. This is supported by the observation that desensitization is paralleled by a significant negative shift in reversal potential of I(K(ACh)). Since the ACh-induced hyperpolarization shows comparable desensitization properties as I(K(ACh)), this novel current-dependent desensitization is a physiologically relevant process, shaping the time course of parasympathetic bradycardia.